Software_Requirement_Specification_Aplikasi_E-commerce_Arsitektur_Rafsya_Berbasis_Website - Yeremia Andrew Sumolang; Rido Nur Rahman; Agung Muhammad Rizki; Fransiskus Xaverius; Intan Oktafiani; Sarah Allya Fawziah; Angela Trinata Saragih (JURNAL TEKNOLOGIA, 2022)
Architects in Indonesia (senior architects and freelance architects) still find it difficult to sell architectural design products. Especially for architects who are outside the island of Java. So we need a website-based e-commerce application specifically for selling architectural product designs for the media for architects and prospective buyers to make buying and selling interactions that are more efficient and effective. This article discusses the software requirements specification for a website-based Rafsya architecture e-commerce application. The purpose of this article is to design an application that can make it easier for prospective customers to choose a house design, make it easier for prospective buyers to find architect services, and provide job vacancies as well as architect promotion media. The research methods used are interviews, surveys, and literature studies. The results of this research are requirements specification, physical data model, application design. Keywords: requirements, architecture, design